THE IMPLEMENTATION OF LEARNING THROUGH AUDIOVISUAL MEDIA IN ELEMENTARY SCHOOL STUDENTS TO FOSTER LEARNING ENTHUSIASM - Desy Ravita; Siti Mayanh Sari; Jonni Sitorus; Sariakin Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT Learning in modern times has undergone significant development. The learning process is no longer teacher-centered but student-centered. As educators, we must be able to design learning materials that align with the advancing technology. Currently, if learning is only teacher-centered and presented with theoretical explanations, students tend to lose enthusiasm for engaging in the learning process. Therefore, audiovisual media, in the form of educational videos, can support active, meaningful learning and foster high enthusiasm for learning. This research aims to: 1) describe the level of student enthusiasm in learning through audiovisual media, and 2) identify the impact and student interest in audiovisual-based learning media in educational activities. This study was conducted at SDN 22 Banda Aceh. The research type is descriptive qualitative, using data collection techniques such as direct observation, interviews, and documentation. The research results show that learning dominated by lectures tends to cause students to lose attention and become disengaged. The results indicate that: 1) after learning was presented using audiovisual media in the form of educational videos, three out of four students were very happy, enthusiastic, and engaged in the learning process with the help of the educational videos, while only one student showed less interest. 2) It can be concluded that audiovisual learning media is capable of fostering student enthusiasm in elementary school education.